Evaluation for anti-cracking performance of polyurethane grout based on overlay test - Zhou, Kun; Liang, Hao; Huang, Feiheng; Cheng, Ziqing (Frontiers in Built Environment, 2024)
Polyurethane grouting has garnered increasing attention in road maintenance, owing to its exceptional interfacial adhesion, mechanical robustness, and chemical resilience. In comparison to conventional SBS-modified asphalt, polyurethane grout offers superior durability and demonstrates an enhanced capacity to inhibit crack propagation within asphalt mixtures. This study investigates the anti-cracking performance of polyurethane grout in comparison to traditional SBS-modified asphalt, utilizing the Overlay Test (OT) to simulate real-world conditions of reflective cracking in asphalt pavements. Results demonstrate that polyurethane grout significantly enhances the crack resistance of asphalt mixtures, manifesting superior durability and resistance to crack propagation at a controlled temperature of 25°C, with a marked increase in the number of loading cycles relative to the control. However, the performance of polyurethane grout is notably diminished under adverse conditions of low temperatures and water immersion. The investigation employs a multi-index evaluation, with gray correlation analysis delineating the efficacy of various indices in appraising crack resistance. Recommending the use of loading cycles, allowable failure times, and cumulative fracture energy as key metrics.